Ensinando a gostar da geometria utilizando o geoplano - SILVA, Cleudiane Priscila Silva da (2024)
The process of teaching and learning Geometry is a great challenge for both teachers and students at different levels. The present investigation aims to explore the teaching-learning process using the geoplane to teach Regular Polygons to 6th year students, establishing a connection with how students can learn to relate concrete knowledge with abstract knowledge, in a meaningful and lasting way. To this end, a qualitative, descriptive case study was carried out. The work was carried out through field research, in a 6th year class at Escola Municipal de Ensino Fundamental Prof. Orlando Moisés, located in the rural area of the municipality of Salinópolis in the state of Pará. In the end, it is concluded that throughout this work applied in the classroom, the geoplane constitutes a dynamic means for students to explore the proposed challenges, to the extent that they could make, redo and undo figures and calculate area and perimeter with great ease.